DIMENSIONS OF THE MARKET RISK - Danu, Cornelia Marcela (Studies and Scientific Researches. Economics Edition, 2014)
The present work presents the concept approach and the types of the market risks, considering the representatives of the two correlative dimensions of the market: the supply and the demand. This approach dissociates from the other ways to define and to manage the market risks by the message that it communicates: all the types of risk caused by the market activities are market risks. These are anthropic risks, based on information and decision. From the point of view of source, the market risks or the decisional risks have the actions of the deciders (natural person or legal person) to achieving the personal goals or mission or the objectives of the firm which they represent. The market risks are those which pose a threat to the attainment of the major objectives or purposes and to maximizing of advantages: the utility for the consumer and profit for the enterprise. The results of the dynamic interdependences are determined by the optimal management of each type of risk, taking into account the system of risks and the potential for transformation of the risk-cause in risk-effect and vice versa.